Pelatihan Pembuatan Nanas Toga sebagai Upaya Pemberdayaan Perempuan di Desa Gunungjaya - Devia Arbarista Rismawati; Yulia Cahyaningrum; M Fikri Amrullah; Sugeng Riyadi (Universitas Negeri Semarang, 2026)
This community service activity aims to optimize the potential of pineapples in Gunungjaya Village by developing